Menyelami Dasar-Dasar Logika: Pondasi Kritis Dalam Berfikir - Agustinus Tandi la’bi’; Ester Novitadesi; Mozes Lawalata (International Forum of Researchers and Lecturers, 2024)
This article explores the important role of logic as a critical foundation in thinking. Logic is a branch of philosophy that studies the rules of correct and valid reasoning. In a world that is complex and full of information, the ability to think critically is becoming increasingly important. Logic helps individuals to understand the structure of arguments, recognize errors in reasoning, and reach rational conclusions. By learning the basics of logic, a person can hone their thinking abilities, improve problem-solving abilities, and strengthen communication skills. This article discusses basic concepts in logic, such as statements, arguments, and common logical errors, as well as the benefits of learning logic in everyday life and in various scientific disciplines. With a strong understanding of logic, individuals can become more critical, analytical, and effective thinkers in facing the complex challenges of the modern world.